Clinical Audit of Denosumab Biosimilar for Aggressive GCT of Bone: A Tertiary Care Center Retrospective Analysis - Singh, Rajesh B.; Jagannathan, Saravana K.; Vineet, Kumar (South Asian Journal of Cancer, 2025)
Giant cell tumor of bone (GCTB) is a locally aggressive tumor with a high recurrence rate. Using denosumab or its biosimilar in a neoadjuvant setting can facilitate limb-preserving surgery and reduce recurrence rates, with minimal side effects.In this clinical audit, we retrospectively analyzed the impact of denosumab biosimilar (DB) on Campanacci grade 3 GCTB, the most aggressive form of these tumors.Means and standard deviations were used for normally distributed continuous variables, medians and ranges for nonnormal continuous variables, and percentages for categorical variables.All cases received two doses of DB on days 0 and 14, resulting in a mean lesion size reduction of 17.75%.Our findings suggest that this treatment regimen can significantly improve outcomes for patients with aggressive GCTB, aiding orthopaedic oncologists in managing these challenging cases more effectively.
Keywords: GCT; denosumab; biosimilar; tumor; recurrence